Unravelling protein aggregation as an ageing related process or a neuropathological response - Trigo, Diogo (2019)
Protein aggregation is normally associated with amyloidosis, namely motor neurone, Alzheimer's, Parkinson's or prion diseases. However, recent results have unveiled a concept of gradual increase of protein aggregation associated with the ageing process, apparently not necessarily associated with pathological conditions. Given that protein aggregation is sufficient to activate stress-response and inflammation, impairing protein synthesis and quality control mechanisms, the former is assumed to negatively affect cellular metabolism and behaviour. In this review the state of the art in protein aggregation research is discussed, namely the relationship between pathology and proteostasis. The role of pathology and ageing in overriding protein quality-control mechanisms, and consequently, the effect of these faulty cellular processes on pathological and healthy ageing, are also addressed.